Cystatin C at Admission in the Intensive Care Unit Predicts Mortality among Elderly Patients - Dalboni, Maria Aparecida (Hindawi Publishing Corporation, 2013)
Introduction. Cystatin C has been used in the critical care setting to evaluate renal function. Nevertheless, it has also been found to correlate with mortality, but it is not clear whether this association is due to acute kidney injury (AKI) or to other mechanism. Objective. To evaluate whether serum cystatin C at intensive care unit (ICU) entry predicts AKI and mortality in elderly patients. Materials and Methods. It was a prospective study of ICU elderly patients without AKI at admission. We evaluated 400 patients based on normality for serum cystatin C at ICU entry, of whom 234 (58%) were selected and 45 (19%) developed AKI. Results. We observed that higher serum levels of cystatin C did not predict AKI (1.05 ± 0.48 versus 0.94 ± 0.36 mg/L; P = 0.1). However, it was an independent predictor of mortality, H.R. = 6.16 (95% CI 1.46–26.00; P = 0.01), in contrast with AKI, which was not associated with death. In the ROC curves, cystatin C also provided a moderate and significant area (0.67; P = 0.03) compared to AKI (0.47; P = 0.6) to detect death. Conclusion. We demonstrated that higher cystatin C levels are an independent predictor of mortality in ICU elderly patients and may be used as a marker of poor prognosis.